BASLAWÍSH KLASS OQÍWShÍLARÍNÍŃ KRITIKALÍQ PIKIRLEWIN RAWAJLANDÍRÍWDÍŃ TIYKARǴI FORMALARÍ - Babasheva, G.B. (SCIENCE and SOCIETY, 2025)
This article examines the main forms of developing critical thinking in primary school students.
Keywords: critical thinking; curiosity; endurance; exercises; independent thinking; breadth of thinking; depth of thinking; pair work; emotionality of learning; stability of attention